(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Introduction: The COVID-19 pandemic emerged as a major public health crisis and was confirmed to havespread to Bangladesh since March 2020. A large number of hospitalized patients with COVID-19 pneumoniarequire intensive care for respiratory support due to hypoxic respiratory failure. Bangladesh is greatlyfacing multiple challenges to combat the surging pandemic due to lack of experiences and insufficientmedical resources. Reports describing patients admitted to the ICU with COVID-19 in Bangladesh are verylimited. Objective of this study was to determine the clinical characteristics and outcomes of the COVID-19patients admitted at the dedicated intensive care unit of Kurmitola General Hospital, Dhaka for bettercharacterization of COVID-19 infection in critically ill patients in a resource limited setting. Materials and Methods: All the RT-PCR confirmed COVID-19 patients aged >15 years who had beenadmitted to the dedicated COVID intensive care unit of Kurmitola General Hospital, Dhaka from April2020 to October 2020 were included in this retrospective cross-sectional study. The protocol was approvedby the Ethical and Scientific Committee of the institute. The demographic, clinical and treatment data ofall participants were collected and evaluated and mode of treatments were compared between survivorand non-survivor groups. The statistical analysis was carried out using the Statistical Package for SocialSciences version 22.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Results: A total of 294 critically ill COVID-19 patients were admitted to the ICU of Kurmitola generalhospital between April, 2020 to October, 2020. The mean (±SD) age of the patients was 57.4 (±13.1) years,male participants were predominant (71.1%), 74.5% patients had positive contact history, commonpresenting problems were fever (94.5%), cough (83.6%), dyspnoea (80.9%), diarrhoea (60.2%) and chestpain (42.8%). Frequency of different associated co-morbidities like hypertension (49.3%), diabetes mellitus(50.3%), cardiac diseases (34.0%), renal diseases (17.7%), bronchial asthma (33.3%), COPD (40.1%), CVD(24.1%) and obesity (24.1%) were high. The mean (±SD) length of ICU stay of the patients was 7.0 (±4.1)days; 11.6% patients required mechanical ventilation; 63.6% of ICU patients died and 36.4% recovered inthe specified time period. HFNC was provided to 62.6% patients in survivor group and 56.1% in nonsurvivorgroup, 31% of non-survivor patients required non-invasive ventilator support. Requirement ofmechanical ventilation was significantly higher among the non-survivor group (18.7%) than survivorgroup (p <o.oo1). Use of convalescent plasma therapy was significantly higher in survivor group (29.0%)than the non-survivor group (18.7%) (p=0.043). No significant differences regarding anti-viral, monoclonalantibody and anticoagulant therapy were observed between both groups. Conclusion: This retrospective cross-sectional study represented the clinical characteristics and treatmentoutcomes of the critically ill COVID-19 patients at ICU of Kurmitola General Hospital, Dhaka, Frequencyof positive contact history and presence of co-morbidities were high. Death rate was significantly highamong the patients who required mechanical ventilation. Patients of survivor group were significantlybenefited from convalescent plasma therapy. Larger, multicenter, prospective studies with extendedfollow-up should be conducted to verify the study findings. JBSA 2021; 34(1): 12-19